An assestment of outdoor thermal comfort of Baiturrahman Mosque in Banda Aceh / Kamila Bilqis, Laina Hilma Sari and Laila Qadri - Bilqis, Kamila; Sari, Laina Hilma; Qadri, Laila (2018)
The thermal comfort of the outer space is an important thing to study. This would be the same as well as with the inner space of the mosque, especially if the outer space has a function that is tied to the inner space. Baiturrahman Great Mosque is a building of worship that has an outer space with enough important functions in the form of haraam to perform prayers. The thermal comfort evaluation of the outer space of the Baiturrahman Grand Mosque of Banda Aceh is conducted to determine the thermal condition in order to optimize the function of the outer space in relation to thermal comfort. This research uses done by doing literature review, field observation, interview and filing questionnaire as well as make direct measurements about environmental influences such as air temperature, wind speed, solar radiation, humidity and review the influence of the outer space parts such as floor surface and use of imagery associated with external thermal conditions. Based on the design characteristics of the Grand Mosque of Baiturrahman Great Mosque some things that affect thermal comfort such as the use of floor materials, imagery and vegetation elements. Of the various indicators, which most affect the sensation of heat in the outer space of the Baiturrahman Great Mosque is the availability of imagination elements. In areas where perception is perceived to have the highest value +1,4 is a rather warm sensation and in areas without imagery has the highest value of +1.5 is a warm sensation. While the material element affects the sensation of heat in the skin stimulus due to its conductivity. In this case the natural ceramic floor material provides the highest heat stimulus on the skin with an average temperature of 47.3 o C and the lowest temperature is found on the shaded grass material of 28.2 o C.